The Impact of Remittances from Overseas Workers on Economic Expansion at Home: Evidence from Bangladesh (Global Journal of Management and Business Research, 2022)
The goal of this study is to find out how the money that migrant workers from Bangladesh send home affects the country's overall rate of economic growth. This study makes use of the multiple regression model as an analytical strategy for estimating yearly time-series data and parameters from 1999 to 2021. The real-world evidence supports the idea that there is a strong positive link between the money that migrant workers send home and the growth of the economy. Other changes in regulations, like those about gross capital creation and the size of the labor force, are also statistically significant, but they don't include direct foreign investment. This article looks at some important research that shows how important remittances sent by migrant workers are as a way to grow the economy. In addition, the variability of the controls, the length of the research, and the estimating methods used are all different from those used in earlier studies. In conclusion, the empirical findings that have been developed are quite sound.
Keywords: remittances; migrant workers; economic growth; capital creation